Insights into culturally appropriate latent tuberculosis infection (LTBI) screening in NSW: perspectives of Indian and Pakistani migrants. (10th August 2020) - Hall, Julie; Kabir, Tajmmal Muhammad; Shih, Patti; Degeling, Chris
Abstract: Objective : Latent tuberculosis (LTBI) case‐finding and treatment are a focus of TB elimination in Australia. We sought the perspectives of migrants from two high‐burden countries likely to be targeted by this strategy. Methods : To understand perceptions of migrant groups in Australia on LTBI screening, 28 in‐depth interviews were conducted with Indian and Pakistani community members recruited purposively through local organisations in the Illawarra region, New South Wales. Drawing on local TB policy, data collected qualitatively was analysed using framework methodologies. Results : Australia's immigration system prioritises migrants of higher socioeconomic status. Participants supported elimination but perceived TB as a disease of the poor and not relevant to them. Lack of understanding of LTBI and sensitivity to being 'targeted' are further barriers to screening participation. Conclusion : Information provision and targeting rationale are an essential preamble to LTBI screening. Migration appears to modify cultural attitudes to TB, but not significantly. Despite less stigma surrounding TB in Australian contexts, testing privacy and confidentiality, and limiting public identification of specific groups remain important to program acceptability. Implications for public health : Progress towards TB elimination can be enhanced by consulting with targeted communities, using existing networks for communication and service provision; emphasising prevention benefits.